Conductive piezoelectric film, device, and method for manufacturing conductive piezoelectric film
By using conductive layers containing materials such as metal nanowires on the piezoelectric film, combined with wet coating and heat treatment technology, the problems of conductive layer deterioration and uneven transparency caused by high-temperature heating are solved, and a high-transparency and high-conductive voltage is achieved Electric film, suitable for touch panels and other applications.
Patent Information
- Application Number
- CN202380037206.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-18
- Filing Date
- 2023-05-17
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, when forming a piezoelectric film for a touch panel, high-temperature heating treatment leads to deterioration of the electrical resistance and uneven transparency of the conductive layer, making it difficult to take into account both conductivity and transparency.
A conductive layer containing metal nanowires, conductive polymers, carbon nanotubes and graphene is used to form a conductive layer on the piezoelectric film through wet coating method, with a total light transmittance of more than 80% and a standard deviation of less than 1.4%. Heat treatment was performed at 80°C to control the heat shrinkage, combined with surface modification treatment and clear coating to improve smoothness and adhesion.
It is achieved to improve the conductivity and stability of the conductive layer without damaging transparency, and to suppress uneven transparency, and is suitable for devices such as touch panels and piezoelectric panels.
Smart Images

Figure CN119138128A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive piezoelectric film, a device having the conductive piezoelectric film, and a method for manufacturing the conductive piezoelectric film. Background Art
[0002] Touch panels are widely used as devices that can input information by directly touching an image display unit. A typical form of such a touch panel is a capacitive touch panel that utilizes changes in current capacitance generated between a transparent electrode and a finger (Patent Document 1).
[0003] A transparent conductive film is used in a position detection sensor used in a touch panel. For example, ITO (indium tin oxide) is formed on a PET film by dry coating such as sputtering, and then the crystallinity of the ITO is improved by heat treatment (about 150°C), thereby achieving low resistance and high transmittance.
[0004] Recently, there has been an increasing interest in the technology of simultaneously sensing the position and pressure when a finger or the like touches an operating surface, and a method of combining a pressure detection sensor composed of a piezoelectric sensor with a position detection sensor has been proposed. However, when a piezoelectric film used for a piezoelectric sensor is subjected to a high temperature heat treatment like a PET film, the resistance deteriorates or the color tone of the film is damaged, so it is difficult to use a conductive piezoelectric film formed with ITO by dry coating such as sputtering in a touch panel.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 5-324203 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] As a method for forming a conductive layer that does not require a high-temperature heating treatment, the present inventors have studied a wet coating method of applying a solution containing a conductive substance such as metal nanowires and conductive polymers. However, when the wet coating method is applied to a piezoelectric film to form a conductive layer, it is found that performance deviations occur, especially uneven transparency.
[0010] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a conductive piezoelectric film with suppressed transparency unevenness, a device including the conductive piezoelectric film, and a method for manufacturing the conductive piezoelectric film.
[0011] Technical Solution
[0012] The present inventors have found that the above problems can be solved by providing a conductive piezoelectric film having a conductive layer containing metal nanowires and the like and having a total light transmittance and a standard deviation of the total light transmittance within a specific range, thereby completing the present invention. Specifically, the present invention relates to the following.
[0013] The present invention relates to a conductive piezoelectric film, which comprises a piezoelectric film and a conductive layer stacked on one surface of the piezoelectric film, with a total light transmittance of more than 80% and a standard deviation of the total light transmittance of less than 1.4%, wherein the conductive layer comprises at least one selected from the group consisting of metal nanowires, conductive polymers, carbon nanotubes and graphene.
[0014] The surface waviness Wa of the piezoelectric film at the interface with the conductive layer is preferably 30 μm or less.
[0015] In the conductive piezoelectric film, it is preferred that the absolute value of the heat shrinkage ratio when heat-treated at 80° C. for 30 minutes is less than 1.0% at most.
[0016] The adhesiveness of the conductive layer evaluated based on ASTM D3359 is preferably 4B or more.
[0017] The metal nanowires are preferably silver nanowires.
[0018] The piezoelectric film preferably contains a fluorine-based resin.
[0019] Furthermore, the present invention relates to a device including the conductive piezoelectric film.
[0020] Furthermore, the present invention relates to a method for manufacturing a conductive piezoelectric film, which includes the following steps: applying a solution containing a conductive substance on the surface of a piezoelectric film stacked with a protective film on the opposite side of the protective film to form a conductive layer with a total light transmittance of more than 80%, wherein the conductive substance is selected from at least one of the group consisting of metal nanowires, conductive polymers, carbon nanotubes and graphene.
[0021] In the above step, the water contact angle of the surface on which the solution is applied is preferably 70° or less.
[0022] The protective film preferably has an elastic modulus of 1.0 GPa or more.
[0023] Beneficial Effects
[0024] According to the present invention, it is possible to provide a conductive piezoelectric film having suppressed unevenness in transparency, a device including the conductive piezoelectric film, and a method for manufacturing the conductive piezoelectric film. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 is a cross-sectional view schematically showing a conductive piezoelectric film 1 as one embodiment of the conductive piezoelectric film of the present invention.
[0026] Figure 2 1 is a cross-sectional view schematically showing a conductive piezoelectric film 2 as another embodiment of the conductive piezoelectric film of the present invention. DETAILED DESCRIPTION
[0027] Hereinafter, an embodiment of the present invention (hereinafter referred to as “the present embodiment”) will be described in detail with reference to the drawings, but the present invention is not limited thereto and various modifications can be made without departing from the gist of the invention.
[0028] Conductive piezoelectric film
[0029] The conductive piezoelectric film of the present invention comprises a piezoelectric film and a conductive layer stacked on one surface of the piezoelectric film, the total light transmittance is 80% or more, the standard deviation of the total light transmittance is 1.4% or less, and the conductive layer comprises at least one selected from the group consisting of metal nanowires, conductive polymers, carbon nanotubes, and graphene. It should be noted that in this specification, "stacked" means that as long as the layers are stacked in order, other layers may be stacked between the layers.
[0030] <Characteristics of Conductive Piezoelectric Film>
[0031] The total light transmittance of the conductive piezoelectric film is greater than 80%, and the standard deviation of the total light transmittance is less than 1.4%.
[0032] The higher the total light transmittance of the conductive piezoelectric film, the higher the transparency, and thus it is preferred. The total light transmittance of the film is more preferably 84% or more, further preferably 86% or more, and particularly preferably 90% or more. The upper limit of the total light transmittance is not particularly limited.
[0033] The smaller the standard deviation of the total light transmittance of the conductive piezoelectric film, the smaller the non-uniformity of transparency, and therefore it is preferred. The standard deviation of the total light transmittance of the film is preferably 1.4% or less, more preferably 1.1% or less, further preferably 0.8% or less, and particularly preferably 0.5% or less. The lower limit of the standard deviation of the total light transmittance is not particularly limited.
[0034] In this specification, the total light transmittance of the conductive piezoelectric film is a value measured according to JIS K 7361-1, and can be specifically measured by the method described in Examples described below. The standard deviation of the total light transmittance is a value calculated from the measured total light transmittance.
[0035] The standard deviation of the total light transmittance can be reduced, for example, by laminating a protective film on the surface of the piezoelectric film opposite to the surface on which the solution is applied before applying a solution containing a conductive substance on the piezoelectric film. It is believed that the piezoelectric film has a lower surface smoothness than a film such as PET, and applying the above solution on the surface of such a piezoelectric film will cause uneven transparency. Therefore, it is considered to improve the smoothness of the piezoelectric film by laminating a protective film.
[0036] In addition, for example, before applying a solution containing a conductive substance to the surface of the piezoelectric film, the surface to be coated of the piezoelectric film is subjected to surface modification treatment (corona treatment, plasma treatment, flame treatment, ultraviolet irradiation treatment, etc.), or a transparent coating is formed on the surface of the piezoelectric film on the side to be coated, so that the water contact angle of the surface to be coated is less than 70°, the standard deviation of the total light transmittance can also be reduced. Considering that the wettability of the piezoelectric film to the above-mentioned aqueous solution is low, the above-mentioned solution is repelled and uneven, which will also cause uneven transparency. Therefore, it is believed that by making the water contact angle of the surface to be coated less than 70°, the uneven coating of the above-mentioned solution can be eliminated.
[0037] The surface waviness Wa of the piezoelectric film at the interface with the conductive layer is preferably 30 μm or less, and more preferably 25 μm or less. The lower limit of the surface waviness Wa is not particularly limited. If the surface waviness Wa is 30 μm or less, the smoothness of the surface of the piezoelectric film is good, the coating of the conductive layer tends to become more uniform, and the unevenness of transparency is easily suppressed.
[0038] It should be noted that in this specification, the surface waviness Wa is the arithmetic mean height of the reference length of the waviness curve as the profile curve. The waviness curve is not the fine concavities and convexities represented by the roughness curve, but represents concavities and convexities of a larger scale (i.e., waviness). The surface waviness Wa can be specifically measured by the method described in the embodiments described below.
[0039] In the conductive piezoelectric film, the maximum absolute value of the heat shrinkage (in any direction) is preferably less than 1.0%, and more preferably less than 0.5%, even when heat treated at 80°C for 30 minutes. The lower limit of the absolute value of the heat shrinkage is not particularly limited. The absolute value of the heat shrinkage in the above range means that the absolute value of the heat shrinkage of the piezoelectric film used is low, and the piezoelectric film is not easy to shrink during the drying process of the coating, so it is easy to obtain a more uniform conductive layer and it is easy to suppress uneven transparency.
[0040] In addition, in this specification, the heat shrinkage rate can be specifically measured by the method described in the Examples mentioned later.
[0041] The thermal shrinkage rate of the conductive piezoelectric film can be reduced by subjecting the piezoelectric film subjected to the polarization treatment to a heat treatment at 130° C. for 1 minute, for example.
[0042] In the conductive piezoelectric film, the adhesiveness of the conductive layer evaluated based on ASTM D3359 is preferably 4B or more.
[0043] It should be noted that, in this specification, the adhesion of the conductive layer refers to the adhesion of the layer adjacent to the conductive layer on the piezoelectric film side and the conductive layer. For example, when the piezoelectric film is adjacent to the conductive layer, it refers to the adhesion of the piezoelectric film and the conductive layer, and when a transparent coating is arranged between the piezoelectric film and the conductive layer, it refers to the adhesion of the transparent coating and the conductive layer. Specifically, the adhesion of the conductive layer can be measured by the method described in the embodiments described later.
[0044] The haze value of the conductive piezoelectric film is preferably 3.0% or less, more preferably 2.5% or less, further preferably 2.0% or less, and particularly preferably 1.5% or less. The lower limit of the haze value is not particularly limited.
[0045] In addition, in this specification, the haze value of a conductive piezoelectric film is a value measured according to JIS K7136, and can be specifically measured by the method described in the Examples described later.
[0046] The sheet resistance of the conductive piezoelectric film is preferably 1000Ω / sq or less, more preferably 600Ω / sq or less, further preferably 400Ω / sq or less, and particularly preferably 200Ω / sq or less. The lower limit of the sheet resistance is not particularly limited, but from the viewpoint of transparency, it is preferably 10Ω / sq or more, more preferably 20Ω / sq or more, and particularly preferably 40Ω / sq or more. In addition, the lower limit of the sheet resistance is not particularly limited, but as a combination of numerical ranges, it is preferably 10Ω / sq or more and 1000Ω / sq or less, more preferably 10Ω / sq or more and 600Ω / sq or less, further preferably 20Ω / sq or more and 400Ω / sq or less, and particularly preferably 40Ω / sq or more and 200Ω / sq or less.
[0047] In addition, in this specification, the sheet resistance of the conductive piezoelectric film is a value measured according to JIS K7194, and can be specifically measured by the method described in the Examples described later.
[0048] The thickness of the conductive piezoelectric film is, for example, preferably greater than 25 μm and less than 120 μm. When the thickness of the piezoelectric film is greater than 25 μm, the amount of charge generated by the piezoelectric effect is greater, and higher piezoelectricity is easily obtained. The thickness of the piezoelectric film is more preferably greater than 30 μm, and further preferably greater than 35 μm. When the thickness of the piezoelectric film is less than 120 μm, the transparency of the piezoelectric film is less susceptible to damage. The thickness of the piezoelectric film is more preferably less than 100 μm, and further preferably less than 80 μm. From the same point of view, the thickness of the piezoelectric film is more preferably greater than 35 μm and less than 80 μm. It should be noted that in this specification, for the thickness of the conductive piezoelectric film and each layer, the thickness is randomly measured at 10 locations from a cross-sectional photograph of the layer taken at 10,000 to 100,000 times using a scanning electron microscope (SEM), and the arithmetic average of the 10 measured thicknesses is used.
[0049] Next, each layer of the conductive piezoelectric film will be described with reference to the drawings.
[0050] Figure 1 1 is a cross-sectional view schematically showing a conductive piezoelectric film 1 as one embodiment of the conductive piezoelectric film. The conductive piezoelectric film 1 has a conductive layer 31 stacked on one surface of a piezoelectric film 11 .
[0051] Figure 2 2 is a cross-sectional view schematically showing a conductive piezoelectric film 2 as another embodiment of the conductive piezoelectric film. The conductive piezoelectric film 2 is different from the conductive piezoelectric film 1 in that a pair of transparent coating layers (a first transparent coating layer 21 and a second transparent coating layer 22) are provided to sandwich the piezoelectric film 11. The other structures are the same as those of the conductive piezoelectric film 1.
[0052] <Piezoelectric film>
[0053] The piezoelectric film 11 is a film (thin film) having piezoelectricity (a property of converting an applied force into a voltage or a property of converting an applied voltage into a force).
[0054] Materials constituting the piezoelectric film 11 include polarizable polar polymers capable of exhibiting piezoelectricity by polarizing molecular dipoles through a polarization treatment generally referred to as a thermal polarization treatment, and stretched chiral polymers capable of exhibiting piezoelectricity by applying a stretching treatment to the chiral polymer. Examples of polarizable polymers include: fluorine-based resins; vinylidene cyanide-based polymers; vinyl acetate-based polymers; odd-numbered nylons such as nylon 9 and nylon 11; polyureas, etc. Examples of stretched chiral polymers include: helical chiral polymers such as polylactic acid; polyhydroxycarboxylic acids such as polyhydroxybutyrate; cellulose derivatives, etc. These can be used alone or in combination of two or more. Among them, the piezoelectric constant d of the piezoelectric film can be easily increased. 33 From the viewpoint of more easily obtaining a piezoelectric effect, a fluorine-based resin is preferred, and a homopolymer of vinylidene fluoride is more preferred.
[0055] Piezoelectric constant d of piezoelectric film 33 It is preferably 10 pC / N or more and 40 pC / N or less. 33 When the piezoelectric constant d is 10 pC / N or more, the amount of charge generated by the piezoelectric effect is greater, so the pressure sensitivity can be further improved. 33 When the piezoelectric constant d is 40 pC / N or less, for example, the decrease in the flatness of the surface of the piezoelectric film caused by the polarization treatment can be further reduced, so the standard deviation of the total light transmittance can be further reduced. 33 It is more preferably 13 pC / N or more and 35 pC / N or less, and even more preferably 15 pC / N or more and 30 pC / N or less. 33 The piezoelectric constant measurement device ("PiezoMeter System PM300", manufactured by PIEZOTEST) is used to clamp the sample at 0.2N and apply a force of 0.15N at 110Hz. 33 The actual measured value of is a positive value or a negative value depending on the front or back of the film to be measured, but the absolute value is described in this specification.
[0056] As fluorine resin, can be listed: polyvinylidene fluoride (PVDF), vinylidene fluoride copolymer (for example vinylidene fluoride / trifluoroethylene copolymer, vinylidene fluoride / trifluoroethylene / chlorotrifluoroethylene copolymer, hexafluoropropylene / vinylidene fluoride copolymer, perfluorovinyl ether / vinylidene fluoride copolymer, tetrafluoroethylene / vinylidene fluoride copolymer, hexafluoropropylene / vinylidene fluoride copolymer, hexafluoropropylene / vinylidene fluoride copolymer, hexafluoropropylene / tetrafluoroethylene / vinylidene fluoride copolymer); tetrafluoroethylene polymer; chlorotrifluoroethylene polymer etc. They can be used alone or in combination of two or more. Among them, from the viewpoints of the height, weather resistance, heat resistance, etc. of the obtained piezoelectricity, polyvinylidene fluoride and / or vinylidene fluoride copolymer are more preferred.
[0057] The piezoelectric constant d of the piezoelectric film 11 33 The piezoelectric constant d of the piezoelectric film 11 can be adjusted mainly by the type of resin contained in the piezoelectric film 11 or the manufacturing conditions (polarization treatment or stretching treatment conditions). For example, among fluorine-based resins, the more structural units derived from vinylidene fluoride are contained in the resin, the greater the piezoelectric constant d of the piezoelectric film 11. 33 In addition, by enhancing the polarization treatment and stretching treatment, the piezoelectric constant d of the piezoelectric film 33 Easy to enlarge.
[0058] The thickness of the piezoelectric film 11 is, for example, preferably greater than 25 μm and less than 120 μm. When the thickness of the piezoelectric film 11 is greater than 25 μm, the amount of charge generated by the piezoelectric effect is greater, and higher piezoelectricity is easily obtained. The thickness of the piezoelectric film 11 is more preferably greater than 30 μm, and further preferably greater than 35 μm. When the thickness of the piezoelectric film 11 is less than 120 μm, the transparency of the piezoelectric film 11 is less likely to be impaired. The thickness of the piezoelectric film is more preferably less than 100 μm, and further preferably less than 80 μm. From the same point of view, the thickness of the piezoelectric film is more preferably greater than 35 μm and less than 80 μm.
[0059] <Conductive layer>
[0060] The conductive layer 31 includes at least one selected from the group consisting of metal nanowires, conductive polymers, carbon nanotubes, and graphene. By including these conductive substances, both conductivity and transparency can be achieved.
[0061] Metal nanowires refer to conductive materials made of metal, shaped like needles or wires, and having a diameter of nanometers. Metal nanowires can be straight or curved. Examples of metal nanowires include silver nanowires, gold nanowires, copper nanowires, nickel nanowires, etc. They can be used alone or in combination of two or more. Among them, silver nanowires are preferred.
[0062] The average diameter, average length and aspect ratio (average length / average diameter) of the metal nanowires are not particularly limited as long as they are within the range of good conductivity and transparency. For example, the average diameter is preferably 10 nm or more and 500 nm or less, more preferably 10 nm or more and 100 nm or less. The average length is preferably 1 μm or more and 300 μm or less, more preferably 1 μm or more and 100 μm or less. The aspect ratio (average length / average diameter) is preferably 10 or more and 10,000 or less, more preferably 100 or more and 5,000 or less. The average diameter and average length of the metal nanowires are the values obtained by measuring the size of 100 arbitrarily selected metal nanowires using a scanning electron microscope as their arithmetic mean.
[0063] As a method for producing metal nanowires, a known production method can be used. For example, in the case of silver nanowires, the polyol method can be used to synthesize by reducing silver nitrate in the presence of polyvinyl pyrrolidone (see Chem. Mater., 2002, 14, 4736-4745). Similarly, gold nanowires can be synthesized by reducing gold chloride hydrate in the presence of polyvinyl pyrrolidone (see J. Am. Chem. Soc., 2007, 129, 1733-1742).
[0064] As the conductive polymer, for example, polythiophene, polypyrrole, polyaniline, polyacetylene, polyparaphenylene, polyparaphenylene vinylene, polyfluorene, etc. can be used. They can be used alone or in combination of two or more. Among them, polythiophene is preferred, and a mixture of poly (3,4-ethylenedioxythiophene) and polystyrene sulfonic acid (PEDOT / PSS) is more preferred.
[0065] The carbon nanotubes are not particularly limited as long as they are within the range that can provide good conductivity and transparency. For example, they may be single-walled carbon nanotubes or multi-walled carbon nanotubes such as double-walled carbon nanotubes. They may be used alone or in combination of two or more.
[0066] Graphene is not particularly limited as long as it can obtain good conductivity and transparency. For example, it can be single-layer graphene or multi-layer graphene. In addition, it can also be graphene oxide, graphene nanoribbon, etc. They can be used alone or in combination of two or more.
[0067] In the conductive layer, other components other than these conductive substances may be used in combination within the range that does not impair its function. As other components, surfactants, surface conditioners, anticorrosive agents, pH adjusters, binder resins, tackifiers, etc. may be listed. In addition, the conductive layer may also contain trace components and inevitable components within the range that does not impair its function.
[0068] The surfactant may be any compound having a surface active function. Examples of the surfactant include nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, etc. These may be used alone or in combination of two or more.
[0069] The surface conditioning agent can be any substance that can prevent surface defects such as bubbles, depressions, pinholes, spots, etc. of the coating film. Examples of the surface conditioning agent include acrylic compounds, vinyl compounds, silicone compounds, fluorine compounds, etc. These can be used alone or in combination of two or more.
[0070] The anticorrosive agent may be any compound that can prevent metal from rusting, and specific examples thereof include imidazoles, benzimidazoles, benzotriazoles, tetrazoles, thiazoles, benzothiazoles, thiadiazoles, thiazolines, etc. These may be used alone or in combination of two or more.
[0071] The pH adjuster is a compound for adjusting the pH of a solution containing a conductive substance, and specific examples thereof include sulfuric acid, acetic acid, sodium hydroxide, potassium hydroxide, ammonia, dimethylamine, ethanolamine, dimethylethanolamine, etc. These can be used alone or in combination of two or more.
[0072] The binder resin can be used without particular limitation as long as it is a resin that can be dissolved or dispersed in a solvent used in a solution containing a conductive substance. Specific examples include acrylic resins, epoxy resins, oxetane resins, polyurethane resins, polyimide resins, melamine resins, silicone resins, vinyl acetate resins, polyvinyl pyrrolidone, polyester resins, polysaccharides and derivatives thereof. These can be used alone or in combination of two or more.
[0073] The thickener may be any compound that can increase the viscosity of the solution containing the conductive material, and specific examples thereof include alkali thickeners, urethane thickeners, etc. These may be used alone or in combination of two or more.
[0074] The thickness of the conductive layer is preferably greater than 100 nm and less than 2 μm, more preferably greater than 200 nm and less than 1 μm. When within the above numerical range, good conductivity is easily obtained, and the transmittance of visible light is likely to become higher. Thus, in order to obtain a conductive piezoelectric film with better transparency, it is preferred to make the thickness of the conductive layer thinner. However, as described above, considering that the piezoelectric film has a lower surface smoothness than films such as PET, if the thickness of the conductive layer is thin, the influence of the deviation of the film thickness becomes greater, which is associated with uneven transparency, etc. That is, if within the above numerical range, uneven transparency is easily produced, and the effect of the present invention is easily exerted.
[0075] It should be noted that in the case of a conductive layer containing metal nanowires, since the metal nanowires are sparsely dispersed, it is easy to make it difficult to measure the thickness. In such a case, the thickness of the coating film composed of other components such as a tackifier and a binder resin is taken as the thickness of the conductive layer.
[0076] <Clear coating>
[0077] The conductive piezoelectric film of the present invention may also include a transparent coating layer.
[0078] The conductive piezoelectric film 2 has a first transparent coating layer 21 on the surface of the piezoelectric film 11 on the conductive layer 31 side, and a second transparent coating layer 22 on the surface of the piezoelectric film 11 on the opposite side of the conductive layer 31 side as a pair of transparent coating layers. That is, the conductive piezoelectric film 2 has a stacked structure in which the second transparent coating layer 22, the piezoelectric film 11, the first transparent coating layer 21, and the conductive layer 31 are stacked in sequence. The thickness, structure, and composition of the first transparent coating layer 21 and the second transparent coating layer 22 may be the same or different. In addition, it is not necessary to have both the first transparent coating layer 21 and the second transparent coating layer 22, and only one of them may be provided.
[0079] Examples of the clear coating layer include a hard coating layer, a primer layer, and a top coating layer. The clear coating layer may be a single layer or a combination of a plurality of layers.
[0080] The hard coating layer or primer layer not only protects the surface of the piezoelectric film from damage and contamination, but also improves transparency (reduces haze) by filling the damage on the surface of the piezoelectric film. In addition, by providing a hard coating layer or primer layer between the conductive layer and the piezoelectric film, the water contact angle of the surface coated with the solution containing the conductive substance can be made less than 70°, which can reduce the standard deviation of the total light transmittance.
[0081] The outer coating can inhibit the metal nanowires from being oxidized by water, air or light.
[0082] The transparent coating layer contains, for example, a cured resin obtained by curing a resin composition. The resin composition preferably contains at least one selected from a thermosetting resin composition, an ultraviolet curable resin composition, and an electron beam curable resin composition. The resin composition may also contain at least one selected from a (meth)acrylate resin, a urethane resin, an epoxy resin, a phenoxy resin, and a melamine resin.
[0083] The resin composition is, for example, a composition containing a curable compound having an energy ray reactive group such as a (meth)acryloyl group, a vinyl group, etc. It should be noted that the expression of a (meth)acryloyl group refers to at least one of an acryloyl group and a methacryloyl group. Preferably, the curable compound contains a multifunctional monomer or oligomer containing two or more, preferably three or more functional groups that react with energy rays in one molecule.
[0084] When a resin composition that is cured by energy rays is used, the resin composition can be cured by irradiating energy rays such as ultraviolet rays. Therefore, it is preferable to use such a resin composition also from the viewpoint of the production process.
[0085] The curable compound preferably contains an acrylic monomer. Examples of the acrylic monomer include urethane-modified acrylates and epoxy-modified acrylates.
[0086] From the viewpoints of improving the strength of the coating film and improving the adhesion with the conductive layer, the resin composition preferably contains microparticles (organic microparticles and / or inorganic microparticles). As organic microparticles, for example, silicone microparticles, cross-linked acrylic microparticles, and cross-linked polystyrene microparticles can be listed. As inorganic microparticles, for example, silicon dioxide particles, calcium carbonate particles, aluminum oxide particles, zirconium oxide particles, titanium oxide particles, and iron oxide particles can be listed. They can be used alone or in combination of two or more.
[0087] If the transparent coating layer is too thin, it is difficult for the transparent coating layer to fully cover the fine concavo-convex shapes on the surface of the piezoelectric film, and the effect of reducing the haze of the piezoelectric film may not be fully obtained. In addition, if the transparent coating layer is too thick, the piezoelectricity of the conductive piezoelectric film sometimes becomes insufficient. Therefore, the thickness of the transparent coating layer is preferably greater than 0.20 μm and less than 3.5 μm, more preferably greater than 0.35 μm and less than 2.5 μm, and further preferably greater than 0.50 μm and less than 1.5 μm. By making the thickness of the transparent coating layer within the above range, in the conductive piezoelectric film, sufficient piezoelectricity and transparency corresponding to the application can be taken into account.
[0088] The preferred embodiments of the present invention have been described above, but the present invention is not limited to the above embodiments. For example, the above-mentioned conductive piezoelectric film 2 has a pair of transparent coatings, but may also include only one of the first transparent coating 21 and the second transparent coating 22. In addition, from the viewpoint of improving the durability of the conductive layer 31, the conductive piezoelectric films 1 and 2 may also include a transparent coating as an outer coating on the surface of the conductive layer 31 opposite to the piezoelectric film 11. Furthermore, on the conductive piezoelectric films 1 and 2, any layer other than the above-mentioned layer may be provided at any position within the range that does not significantly impair its function.
[0089] <Applications of Conductive Piezoelectric Film>
[0090] The conductive piezoelectric film of the present invention is preferably used in piezoelectric panels including touch panels of capacitive type and resistive type, pressure sensors, actuators for tactile devices, piezoelectric vibration power generation devices, flat speakers and other devices. The piezoelectric panel further has a common display panel unit such as LCD (Liquid Crystal Display) under the conductive piezoelectric film. The device is preferably used in mobile phones, smart phones, mobile information terminals, tablet PCs, notebook computers, ATM (Automated Teller Machine), FA (Factory Automation) equipment, OA (Office Automation) equipment, medical equipment, car navigation systems, etc.
[0091] 《Method for manufacturing conductive piezoelectric film》
[0092] The conductive piezoelectric film of the present invention can be produced by a method including the step of applying a solution containing a conductive substance on the surface of the piezoelectric film on which a protective film is laminated, opposite to the protective film, to form a conductive layer having a total light transmittance of 80% or more.
[0093] As the piezoelectric film, the piezoelectric film described in <Piezoelectric film> can be used. When a piezoelectric film containing a fluorine-based resin is used, the piezoelectric film can be produced by the following method.
[0094] When manufacturing a piezoelectric film containing a fluorine-based resin, the piezoelectric film can be obtained by polarizing the film containing the fluorine-based resin. The film containing the fluorine-based resin can be a stretched film or an unstretched film. In this embodiment, from the perspective of showing a high piezoelectric effect, it is preferred to stretch the film containing the fluorine-based resin and then polarize it.
[0095] The film containing fluorine resin can be manufactured by any method such as melt extrusion, hot pressing, solution casting, etc. Among them, from the viewpoint of easily obtaining a piezoelectric film with a thickness above the prescribed value, the film containing fluorine resin is preferably manufactured by melt extrusion. In the melt extrusion method, the fluorine resin and any additives can be heated and melted in the barrel of the extruder, and then extruded from the die head to obtain a film.
[0096] The obtained film has a structure in which α-type crystals (the main chain is a helical structure) and β-type crystals (the main chain is a planar zigzag structure) are mixed. β-type crystals have a large polarization structure. By stretching the film, α-type crystals can be converted into β-type crystals. In the stretching process, in order to make the fluororesin into β-type crystals, it is preferred to adjust the stretching ratio as needed. The stretching direction can be the TD direction or the MD direction, and the MD direction is more preferred.
[0097] The stretching method is not particularly limited, and a known stretching method such as a tenter method and a roll method may be used.
[0098] The stretching ratio can be, for example, 3.0 times or more and 6.0 times or less. If the stretching ratio is 3.0 times or more, it is easy to adjust the thickness and polarizability of the film to a more appropriate range. If the stretching ratio is 3.0 times or more, the dislocation of the β-type crystal becomes more sufficient, not only is it easy to show higher piezoelectricity, but also the transparency can be further improved. If the stretching ratio is 6.0 times or less, the fracture caused by stretching can be further suppressed.
[0099] The obtained stretched film is preferably subjected to polarization treatment. The polarization treatment can be performed, for example, by applying a DC voltage between a ground electrode and a needle-shaped electrode. The voltage can be adjusted according to the thickness of the stretched film, and can be, for example, 1 kV or more and 50 kV or less.
[0100] As described above, in this embodiment, a piezoelectric film can be obtained by subjecting a stretched film to a polarization treatment.
[0101] The piezoelectric film laminated with the protective film can be obtained by, for example, a method of laminating the protective film and the piezoelectric film using a laminator, a multi-coater, or the like.
[0102] The elastic modulus of the protective film is preferably 1.0 GPa or more, more preferably 2.0 GPa or more, and further preferably 2.5 GPa or more. By laminating the protective film having an elastic modulus of 1.0 GPa or more to the piezoelectric film, the surface of the piezoelectric film can be appropriately flattened. Thus, the unevenness of the transparency of the conductive piezoelectric film can be further suppressed.
[0103] In addition, in this specification, the elastic modulus of a protective film means the tensile elastic modulus of a substrate, and is a value measured according to JIS K 7127:1999.
[0104] As the substrate of the protective film, there is no particular limitation as long as the elastic modulus satisfies the above range, and examples thereof include: polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate; polyolefins such as polyethylene (PE) and polypropylene (PP); halogen-containing polymers such as polyvinyl chloride (PVC) and polyvinylidene fluoride (PVDF); acrylic polymers such as polymethyl methacrylate; styrene polymers such as polystyrene and styrene-methyl methacrylate copolymer. Among them, PET and PP are preferred, and PET is more preferred from the viewpoint of higher elastic modulus. In addition, these films may be non-stretched films, and more preferably biaxially stretched films.
[0105] The thickness of the substrate of the protective film is preferably 30 μm or more, more preferably 50 μm or more. In addition, the thickness of the substrate is preferably 300 μm or less, more preferably 150 μm or less. If it is within the above range, the smoothness of the piezoelectric film is further improved, and the unevenness of the transparency of the conductive piezoelectric film can be further suppressed.
[0106] The conductive material is not particularly limited, but preferably forms a transparent (for example, a total light transmittance of 80% or more) conductive layer (transparent conductive material), for example, the above-mentioned silver nanowires, conductive polymers, carbon nanotubes, graphene, etc. Preferably, carbon black, graphite, etc. that form an opaque conductive layer are not contained.
[0107] As a solvent used in a solution containing a conductive substance, there is no particular limitation as long as the conductive substance can be dispersed, and it can be appropriately selected according to the desired viscosity, drying speed, etc. For example, in the case of silver nanowires, alcohol solvents such as water, ethanol, methanol, and 1-propanol can be used. In the case of conductive polymers, in addition to water and alcohol solvents, ether solvents such as propylene glycol dimethyl ether, nitrogen-containing solvents such as N-methylpyrrolidone, and sulfur-containing solvents such as dimethyl sulfoxide can also be used. They can be used alone or in combination of two or more. In addition, in addition to the conductive substance, the solution can also contain the above-mentioned other components.
[0108] The content of the conductive substance in 100% by mass of the solution is not particularly limited and can be appropriately set in consideration of coating properties, drying properties, etc., and is, for example, 0.01% by mass or more and 5% by mass.
[0109] The method for applying the solution containing the conductive material is not particularly limited and can be carried out by a known method. Examples of the coating method include an extrusion nozzle method, a scraper method, a doctor blade method, a rod coating method, a kiss-coating method, a kiss reverse method, a gravure roll coating method, a dip coating method, a reverse roll coating method, a direct roll coating method, a curtain method, and an extrusion method.
[0110] As a drying method after coating, any appropriate drying method (e.g., natural drying, air drying, heating drying) can be adopted. For example, in the case of heating drying, in order to prevent the resistance of the piezoelectric film from deteriorating or the color tone of the film from being damaged, for example, the drying temperature is 50° C. to 130° C. and the drying time is 0.5 minute to 10 minutes.
[0111] Since the piezoelectric film has low wettability to a solution containing a conductive substance, the solution is repelled and uneven, which may cause uneven transparency, so the water contact angle of the surface coated with the solution is preferably 70° or less. It should be noted that by making the water contact angle below 70°, the adhesion of the conductive layer is also easy to become good. It should be noted that in this specification, the water contact angle refers to the use of a contact angle meter FACE CA-V (manufactured by Kyowa Interface Science Co., Ltd.), adding a pure water droplet (2.0μL) to the surface, measuring the contact angle 10 times after 3 seconds of addition, and averaging the value.
[0112] As methods for making the water contact angle of the surface coated with the above-mentioned solution be less than 70°, there can be listed methods of performing surface modification treatments such as corona treatment, plasma treatment, flame treatment, ultraviolet irradiation treatment, etc. on the surface of the piezoelectric film to be coated, and methods of forming a transparent coating on the surface of the piezoelectric film to be coated.
[0113] The transparent coating layer can be prepared by applying a solution or dispersion of the resin composition on the surface of the piezoelectric film and drying to cure the resin composition. The application can be performed in the same manner as the application of the solution containing the conductive substance.
[0114] After the conductive layer is formed by the above process, the protective film may be peeled off from the piezoelectric film. The peeling method is not particularly limited. After peeling off the protective film, a transparent coating may be formed on the peeling side of the piezoelectric film and the surface of the conductive layer on the opposite side of the piezoelectric film.
[0115] Example
[0116] The present invention will be further described below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0117] The properties of the conductive piezoelectric film of the present invention were measured by the following method. The results are shown in Table 1.
[0118] <Physical Property Evaluation>
[0119] (Surface waviness)
[0120] The surface waviness Wa (μm) of the conductive layer side of the conductive piezoelectric film of the embodiment and the comparative example was measured using a 3D shape measuring machine ("VR-5000" manufactured by Keyence Co., Ltd.) and a multi-file analysis application ("VR-H3CA" manufactured by Keyence Co., Ltd.). A test piece cut into a size of 50 mm × 50 mm was placed on a stage with the surface of the conductive layer as the surface, and the four corners of the test piece were fixed with tape without applying tension. As a pre-processing, a reference plane was set by specifying multiple points, and the surface shape correction was performed with a correction intensity of 5 for waviness removal, and smoothing was performed with a simple average of 3×3. The measurement was performed by photographing with a low-magnification camera. The measurement was carried out under the conditions of a multi-line roughness mode, 5 peripheral roots, 70 skipped intervals, a horizontal area (TD direction), and no truncation. The measurement was carried out three times, and the arithmetic mean was taken as the surface waviness Wa.
[0121] (Heat shrinkage)
[0122] According to the test method of JIS K 7133, the conductive piezoelectric film is cut into a size of 100mm×100mm, and the distance between the two markings printed on the cut test piece in the longitudinal and transverse directions before the test (L0 and T0) is measured. It should be noted that the flow direction of the film when the conductive layer is formed is set to the longitudinal direction, and the right angle direction is set to the transverse direction. Then, after heating in a hot air drying furnace heated to a specified temperature (80°C) for a specified time (30 minutes), the state is adjusted at room temperature for at least 30 minutes, and the distance between the longitudinal and transverse markings (L and T) is measured again. The changes in the distance between the longitudinal and transverse markings (ΔL and ΔT) of the above test piece are calculated by the following formulas (1) and (2).
[0123] ΔL=[(L-L0) / L0]×100(%) (1)
[0124] ΔT=[(T-T0) / T0]×100(%) (2)
[0125] Then, the change in the distance between the marking lines in the longitudinal direction (ΔL) is taken as the heat shrinkage rate in the longitudinal direction (MD) of the film, and the change in the distance between the marking lines in the transverse direction (ΔT) is taken as the heat shrinkage rate in the transverse direction of the film. In any of the embodiments and comparative examples, the absolute value of the heat shrinkage rate in the transverse direction is smaller than the absolute value of the heat shrinkage rate in the longitudinal direction, so the absolute value of the heat shrinkage rate in the longitudinal direction is the largest.
[0126] (Adhesion)
[0127] The adhesion of each conductive piezoelectric film was evaluated using the cross-cutting method. In the conductive layer of each conductive piezoelectric film, 11 lines with a spacing of 1 mm were cut vertically and horizontally with a cutter to produce 100 grids, and then a tape (Cellotape (registered trademark) manufactured by NICHIBAN Co., Ltd., adhesive force 4.01 N / 10 mm) was attached and peeled off. Based on ASTM D3359, the proportion of the conductive layer peeled off from the conductive piezoelectric film was evaluated according to the following evaluation criteria.
[0128] 0B: 65% or more peeling.
[0129] 1B: 35% or more and less than 65% peeling.
[0130] 2B: 15% or more and less than 35% peeling.
[0131] 3B: 5% or more and less than 15% peeling.
[0132] 4B: Less than 5% peeling.
[0133] 5B: No peeling.
[0134] (Sheet resistance)
[0135] The electrical resistance (Ω / sq) of each of the conductive piezoelectric films of Examples and Comparative Examples was measured using a resistivity meter ("LorestaGP MCP-T610", manufactured by NITTOSEIKO ANALYTECH Co., Ltd.) in accordance with JIS K 7194. The resistance was measured three times, and the average value of the three times was determined as a representative value.
[0136] <Optical Characteristics Evaluation>
[0137] (Total light transmittance)
[0138] The total light transmittance (%) of each of the conductive piezoelectric films of Examples and Comparative Examples was measured using a haze meter ("NDH7000SPII", manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7361-1. 15 points were measured on a 10 cm x 15 cm test piece, and the arithmetic mean was determined as a representative value.
[0139] The standard deviation of the total light transmittance was calculated based on the following formula.
[0140] [Formula 1]
[0141]
[0142] (In the formula, s represents the standard deviation, n represents the number of measurement points, and x i represents the total transmittance of each measuring point, x ave It represents the average value of the total light transmittance at each measurement point)
[0143] (Haze value)
[0144] The haze value (%) of each of the conductive piezoelectric films of Examples and Comparative Examples was measured using a haze meter ("NDH7000SPII", manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7136. Fifteen points were measured on a 10 cm x 15 cm test piece, and the arithmetic mean was determined as a representative value.
[0145] [Example 1]
[0146] A resin film (thickness 120 μm) formed of polyvinylidene fluoride (manufactured by KUREHA Co., Ltd.) having a logarithmic viscosity of 1.1 dl / g was uniaxially stretched to a stretching ratio of 4.2 times. After stretching, a DC voltage was applied between the ground electrode and the needle electrode while increasing the DC voltage from 0 kV to 12.0 kV, thereby polarizing the film. The polarized film was further heat-treated at 130°C for 1 minute to obtain a piezoelectric film with a thickness of 40 μm. The d 33 It is 14.0pC / N, and the water contact angle on the surface is 84°.
[0147] Next, a protective film (substrate: polyethylene terephthalate, elastic modulus: 3800 MPa, thickness: 125 μm) was laminated to the piezoelectric film using a multi-coater and then rolled into a roll to obtain a laminated film. The multi-coater was set to a line speed of 5 m / min and a laminating roll contact pressure of about 0.3 N. Furthermore, by applying corona treatment to the surface of the piezoelectric film side of the laminated film, a laminated film having a water contact angle of 70° on the surface of the piezoelectric film side was obtained.
[0148] Referring to the method described in Chem. Mater., 2002, 14, 4736-4745, silver nanowires with an average diameter of 30 nm and an average length of 9.5 μm were prepared, filtered with a filter, washed with water, and then dispersed in ethanol to prepare a silver nanowire dispersion (silver nanowire content: 0.2 mass %). Furthermore, a silver nanowire ink containing 63 mass % of the silver nanowire dispersion and 37 mass % of a dispersion medium (ultrapure water) containing a thickener and a surfactant was prepared.
[0149] The prepared silver nanowire ink was applied to the surface on the piezoelectric film side of the laminated film using a bar coater so as to have a wet thickness of 18 μm, and dried at 80° C. for 4 minutes.
[0150] Next, after the protective film was peeled off from the piezoelectric film, a UV curable resin composition containing amorphous silicon dioxide and made of acrylic resin was applied to the surface of the piezoelectric film from which the protective film was peeled off, and dried at 80°C for 2 minutes. The UV irradiation device CSOT-40 (manufactured by GS Yuasa Co., Ltd.) was used at 400 mJ / cm 2 The dried coating film was irradiated with UV with a cumulative light amount of, thereby obtaining a conductive piezoelectric film having a 200 nm thick conductive layer on one surface of the piezoelectric film and a 0.7 μm thick transparent coating layer on the other surface.
[0151] [Example 2]
[0152] A conductive piezoelectric film having a 160 nm thick conductive layer on one surface of the piezoelectric film and a 0.7 μm thick transparent coating on the other surface was obtained in the same manner as in Example 1 except that the wet thickness of the silver nanowire ink was changed to 11 μm.
[0153] [Comparative Example 1]
[0154] In the same manner as in Example 1, a piezoelectric film having a thickness of 40 μm was obtained.
[0155] The prepared silver nanowire dispersion was applied to one surface of the piezoelectric film using a bar coater so as to have a wet thickness of 25 μm, and dried at 80° C. for 4 minutes to obtain a conductive piezoelectric film.
[0156] [Comparative Example 2]
[0157] A conductive piezoelectric film was obtained in the same manner as in Comparative Example 1 except that the wet thickness of the silver nanowire dispersion was changed to 18 μm.
[0158] [Example 3]
[0159] A UV curable resin composition containing amorphous silica and made of acrylic resin was applied to one side of the piezoelectric film obtained in the same manner as in Example 1, and dried at 80°C for 2 minutes. A UV irradiation device CSOT-40 (manufactured by GS Yuasa Co., Ltd.) was used at 400 mJ / cm 2 The dried coating film was irradiated with UV light at a cumulative light intensity of , thereby forming a clear coating layer a. Next, a protective film was laminated on the surface of the clear coating layer a in the same manner as in Example 1 to obtain a laminated film.
[0160] A UV curable resin composition containing amorphous silica and made of acrylic resin was applied to the piezoelectric film side of the laminated film and dried at 80°C for 2 minutes. A UV irradiation device CSOT-40 (manufactured by GS Yuasa Co., Ltd.) was used at 400 mJ / cm 2 The dried coating film is irradiated with UV light with a cumulative light intensity of to form a clear coating layer b.
[0161] Next, a conductive polymer (PEDOT:PSS) dispersion having a solid content concentration of 2.5% by mass was applied to the surface of the transparent coating b in a wet thickness of 25 μm using a rod coater and dried at 80°C for 4 minutes, thereby obtaining a conductive piezoelectric film having a transparent coating layer with a thickness of 0.7 μm on both surfaces of the piezoelectric film and a conductive layer with a thickness of 0.7 μm on one surface of the piezoelectric film.
[0162] [Example 4]
[0163] In the same manner as in Example 1, a laminated film in which the protective film and the piezoelectric film were bonded together was obtained.
[0164] A UV curable resin composition containing amorphous silica and made of acrylic resin was applied to the piezoelectric film side of the laminated film and dried at 80°C for 2 minutes. A UV irradiation device CSOT-40 (manufactured by GS Yuasa Co., Ltd.) was used at 400 mJ / cm 2 The dried coating film was irradiated with UV light with a cumulative light amount of 10 μm to form a transparent coating. Then, a conductive polymer (PEDOT:PSS) dispersion having a solid content concentration of 2.5% by mass was applied to the surface of the transparent coating with a wet thickness of 10 μm using a rod coater, and dried at 80°C for 4 minutes, thereby obtaining a conductive piezoelectric film having a transparent coating with a thickness of 0.7 μm and a conductive layer with a thickness of 0.3 μm on one surface of the piezoelectric film.
[0165] [Comparative Example 3]
[0166] In the same manner as in Example 1, a piezoelectric film having a thickness of 40 μm was obtained.
[0167] A conductive piezoelectric film was obtained by coating one surface of the piezoelectric film with a conductive polymer (PEDOT:PSS) dispersion having a solid content of 2.5% using a bar coater to a wet thickness of 52 μm and drying at 80° C. for 4 minutes. It should be noted that sheet resistance is difficult to measure.
[0168] [Table 1]
[0169]
[0170] As shown in Table 1, in Examples, the standard deviation of the total light transmittance was low. Therefore, according to the present invention, it was confirmed that a conductive piezoelectric film with suppressed transparency variation can be obtained.
[0171] Description of Reference Numerals
[0172] 1, 2: conductive piezoelectric film; 11: piezoelectric film; 21: first transparent coating layer; 22: second transparent coating layer; 31: conductive layer.
Claims
1. A conductive piezoelectric film comprising a piezoelectric film and a conductive layer stacked on one surface of the piezoelectric film, The total light transmittance of the conductive piezoelectric film is more than 80%. The standard deviation of the total light transmittance of the conductive piezoelectric film is less than 1.4%, The conductive layer includes at least one selected from the group consisting of metal nanowires, conductive polymers, carbon nanotubes, and graphene.
2. The conductive piezoelectric film according to claim 1, wherein: The piezoelectric film has a surface waviness Wa of 30 μm or less at an interface with the conductive layer.
3. The conductive piezoelectric film according to claim 1 or 2, wherein: The absolute value of the thermal shrinkage rate when heat-treated at 80°C for 30 minutes is less than 1.0% at most.
4. The conductive piezoelectric film according to claim 1 or 2, wherein: The adhesiveness of the conductive layer evaluated based on ASTM D3359 was 4B or more.
5. The conductive piezoelectric film according to claim 1 or 2, wherein: The metal nanowires are silver nanowires.
6. The conductive piezoelectric film according to claim 1 or 2, wherein: The piezoelectric film contains a fluorine-based resin.
7. A device comprising the conductive piezoelectric film according to claim 1 or 2.
8. A method for manufacturing a conductive piezoelectric film, comprising the following steps: A solution containing a conductive substance is applied to the surface of a piezoelectric film stacked with a protective film on the opposite side of the protective film, thereby forming a conductive layer with a total light transmittance of more than 80%, wherein the conductive substance contains at least one selected from the group consisting of metal nanowires, conductive polymers, carbon nanotubes and graphene.
9. The method for manufacturing a conductive piezoelectric film according to claim 8, wherein: In the above step, the water contact angle of the surface on which the above solution is applied is 70° or less.
10. The method for manufacturing a conductive piezoelectric film according to claim 8 or 9, wherein: The protective film has an elastic modulus of 1.0 GPa or more.
Citation Information
Patent Citations
Electrostatic capacity type touch panel
JP1993324203A
